KAJIAN KEBIJAKAN ALAT DAN MESIN PERTANIAN - Armansyah H. Tambunan; E. Namaken Sembiring (PERTETA, 2007)
ABSTRACT The development of agricultural mechanization In Indonesia is still very low, even though it is believed that a proper application of agricultural mechinery can improve agricultural productivity and netional competitiveness significantiy. The development of agro-machinery industry is also very low due to unfavorable policy. This paper disclose the trend of agricultural mechanization development in Indonesia and the policy that may influence the trend. The paper concluded that (1) procurement system of agro-machinery should take Into account its appropriateness to the local requirement and condition, (2) lnter-sectoral regulation should consider the possibility to enhance local and domestic agro-mechinery industry. and (3) the local government should establish an mtersectoral technical unit In charge of agricultural mechanization. Keywords: agricultural mechanization, agro-mechinery industr, deregulation Diterima: 20 Agustus 2007, Disetujui: 20 Nopomber 2007